Policy-Makers, Policy-Takers and Policy Tools: Dealing with Behaviourial Issues in Policy Design. Issue 6 (1st November 2020) - Howlett, Michael; Ramesh, M.; Capano, Giliberto
Abstract: Getting the incentives (and disincentives) right in order to ensure proper levels of compliance with government initiatives is a vital assumption of much of the writings on policy design. The assumption, however, overlooks or underestimates other critical factors that affect compliance. This includes policy-makers' behaviour in the social and political construction of policy targets and it also minimizes the complex objective and subjective conditions that affect the target population's attitudes and behaviours in relation to policy-maker aims and goals. The notion of policy-takers as static targets who passively receive policies without trying to evade or even profit from them is as misguided as the assumption that policy-makers only consider evidence on policy tools' effectiveness before selecting them. This article highlights the critical issue surrounding the choice and workings of policy tools and introduces the papers in this special issue. It indicates how they contribute to filling the gaps in our existing understanding of policy tools and advance our understanding of both policy-maker and policy-taker behaviour.